The conception in hemodialysis: medical prognosis and experience of the gynecology-obstetrics department of Oujda on two cases - Ghizlane, Graiti; Hafsa, Taheri; Ibtissam, Bellejdel; Ahmed, Mimouni; Hanane, Saadi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Pregnancy in patients undergoing hemodialysis is a rare occurrence, particularly in Africa where therapeutic resources are limited, and is associated with high maternal-fetal risks. However, the incidence of pregnancies in such patients has increased over the past two decades, with notable improvements in prognosis and fetal survival, reaching 68.4% in some studies. This report describes two cases of pregnancy in patients with end-stage renal disease (ESRD) on chronic hemodialysis at the Mohammed VI university hospital center in Oujda, Morocco. The first case involved a patient whose pregnancy was managed up to 36 weeks of gestation, resulting in the delivery of a live newborn weighing 1600 gm. This outcome was achieved through careful control of blood pressure, management of dry weight, acceptable hemoglobin levels, and optimization of hemodialysis sessions. The second case was more complicated, involving a congenital malformation (omphalocele) that led to preterm labor at 25 weeks. The premature infant, weighing 600 gm, unfortunately died two hours after birth. This observational study highlights the challenges of managing pregnancy in patients on chronic hemodialysis and underscores the importance of multidisciplinary care to improve outcomes. A review of the literature is also provided to contextualize these findings.